2002
DOI: 10.1111/j.1745-6584.2002.tb02539.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Spring Recession Curves

Abstract: Recession curves contain information on storage properties and different types of media such as porous, fractured, cracked lithologies and karst. Recession curve analysis provides a function that quantitatively describes the temporal discharge decay and expresses the drained volume between specific time limits (Hall 1968). This analysis also allows estimating the hydrological significance of the discharge function parameters and the hydrological properties of the aquifer. In this study, we analyze data from pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 7 publications
2
46
0
2
Order By: Relevance
“…The study region is located in a semiarid Mediterranean climate, with an average annual temperature of between 15°C and 18°C (Amit et al 2002). The average precipitation rate in the region is approximately 550 mm/ year (Figure 2), with rainfall events being brief and infrequent, generally between November and March (Gvirtzman 2002).…”
Section: Hydrogeologic Setting and Conceptual Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The study region is located in a semiarid Mediterranean climate, with an average annual temperature of between 15°C and 18°C (Amit et al 2002). The average precipitation rate in the region is approximately 550 mm/ year (Figure 2), with rainfall events being brief and infrequent, generally between November and March (Gvirtzman 2002).…”
Section: Hydrogeologic Setting and Conceptual Model Developmentmentioning
confidence: 99%
“…Padilla et al (1994) have shown how a detailed analysis of the recession portions of spring hydrograph curves can provide important information regarding the storage properties of each of the aquifer components (matrix as base flow, and karst/fractures as quick flow). Work by Amit et al (2002) included quantitative assessments of the recession curves from six springs discharging in Israel. Their results showed that the ratio between the maximum storage volume in the rock matrix to the overall maximum storage of the rock matrix and karst conduits and fractures was generally greater than 0.8.…”
Section: Numerical Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Quick flow characterizes short term stream flow generated from storm rainfall [51], which is calculated based on the runoff curve number method, developed by USDA (United States Department of Agriculture) Natural Resources Conservation Service (the runoff curve number predicts runoff or infiltration from excess rainfall for classified hydrological soil groups). Base flow characterizes stream flow emanating from groundwater.…”
Section: Seasonal Water Yield Modelmentioning
confidence: 99%
“…To determine flow regime of the spring, Mangin's approach (1975) was used. The exponential coefficients a represent inherent aquifer characteristics such as material porosity and internal karstification (Amit et al, 2002;Ková cs et al, 2005;Fiorillo, 2011). The results of analysis are presented in Table 4.…”
Section: Karst Development Classificationmentioning
confidence: 99%